Relationship between state anxiety, heart rate variability, and shooting performance in adolescent shooters - Chaochao Zhao; Kun Wang; Dan Li; Yan Li; Zhuo Wang; Yongsen Liu; Tingran Zhang (BMC Psychology)
Abstract Objective By comparing the differences in pre-competition state anxiety, inter-competition heart rate variability (HRV), and shooting performance of young athletes of different grades, and revealing the correlation between these variables, it provides a potential basis for improving athletes’ shooting performance. Methods A total of 45 adolescent shooters were selected in Chongqing, China, and completed 40 effective shots at self-pace in real shooting scenes. The pre-competition state anxiety, inter-competition HRV, and shooting performance of the athletes were monitored and evaluated respectively. Results (1) There was a significant difference in the pre-match state anxiety of the adolescent shooters, which showed that the cognitive state anxiety and physical state anxiety of the first-level athletes were significantly lower than those of the second-level athletes, while the state confidence was significantly higher than that of the second-level athletes. (2) There were significant differences in HRV of athletes with different sports levels during the competition, showing that the root mean square differences of the standard deviation (RMSSD), total power (TP), and high-frequency of normal (HFn) of the first-level athletes were significantly higher than those of second-level athletes, while low-frequency of normal (LFn) was significantly lower than the latter. (3) The shooting performance of first-level athletes was significantly better than that of second-level athletes. (4) Among adolescent shooters of different grades, there was a significant correlation between pre-competition state anxiety, inter-competition HRV, and shooting performance. The negative dimension of state anxiety was positively correlated with sympathetic activity in HRV, negatively correlated with parasympathetic activity, and negatively correlated with shooting performance. The positive dimension of state anxiety was negatively correlated with sympathetic activity in HRV, positively correlated with parasympathetic activity, and significantly positively correlated with motor performance. Conclusion Adolescent shooters with higher sports levels usually have better pre-competition mental state and emotional regulation ability, and could better maintain autonomic nerve dynamic balance and focus attention resources on shooting tasks during the competition, so it was easier to achieve good shooting performance. Meanwhile, pre-competition state anxiety and HRV during competition could be used as objective indicators to monitor and evaluate the competitive state of young shooters.